Computational prediction of high-risk non-synonymous SNPs in human ApoE and their structural impact on amyloid-β interaction in Alzheimer’s disease pathogenesis - Md. Mainuddin Hossain; Juthi Adhikari; Amit Dutta; Afia Khandaker; Sirajul Islam; Md Masuder Rahman; Abu Zaffar Shibly (PLoS ONE, 2025)
Apolipoprotein E (ApoE) plays a critical role in Alzheimer’s disease (AD) by regulating amyloid beta (Aβ) clearance through direct interaction. Non-synonymous single nucleotide polymorphisms (nsSNPs) in ApoE alter its structure and impair function, contributing to disease progression. This study aimed to identify functionally damaging nsSNPs in the ApoE gene using in silico tools and to assess their structural and binding effects on Aβ in the context of AD progression. A total of 376 nsSNPs were retrieved from dbSNP, ClinVar, and DisGeNET databases. Eight predictive tools (SIFT, PolyPhen-2, PredictSNP, PhD-SNP, PANTHER, PROVEAN, Meta-SNP, and SNAP2) were employed to identify deleterious variants. Protein stability was assessed using I-Mutant 2.0, MUpro, INPS-MD, iStable, and DynaMut2, while structural effects were evaluated via HOPE, MutPred2, Swiss-PDB Viewer, and Missense3D. Domain localization was determined using InterPro. Molecular docking was performed using PyRx and AutoDock Vina. Molecular dynamic simulation (MDS) evaluate binding stability and dynamics through 100-ns by Schrödinger Maestro, analyzing RMSD, RMSF, Rg, SASA. Out of 376 nsSNPs, 10 were consistently predicted as deleterious by all eight computational tools. Among these, two variants (L107P and L122P) were classified as high-risk and located within the receptor-binding domain of ApoE. The receptor-binding domain mediates the interaction between ApoE and Aβ. Molecular docking revealed binding affinities of −5.5 kcal/mol (WT), −5.6 kcal/mol (L107P), and −6.6 kcal/mol (L122P), indicating stronger Aβ binding by L122P. Stronger binding affinity of L122P mutation may promote Aβ aggregation or hinder clearance, potentially contributing to disease severity. MDS showed L122P had the highest structural stability, with the lowest RMSD, RMSF, Rg values and increased SASA, supporting its enhanced interaction with Aβ. These findings suggest that L122P mutation may enhance Aβ aggregation or hinder its clearance, potentially worsening AD and highlight the structural and functional impact of ApoE variants and the need for experimental validation.